Daily Activity Patterns and Co-Occurrence of Duikers Revealed by an Intensive Camera Trap Survey across Central African Rainforests - Houngbégnon, Fructueux G. A.; Cornelis, Daniel; Vermeulen, Cédric; Sonké, Bonaventure; Ntie, Stephan; Fayolle, Adeline; Fonteyn, Davy; Lhoest, Simon; Evrard, Quentin; Yapi, Fabrice; Sandrin, François; Vanegas, Liliana; et al. (Animals (Basel), 2020)
The duiker community in Central African rainforests includes a diversity of species that can coexist in the same area. The study of their activity patterns is needed to better understand habitat use or association between the species. Using camera traps, we studied the temporal activity patterns, and quantified for the first time the temporal overlap and spatial co-occurrence between species. Our results show that: (i) Two species are strongly diurnal: Cephalophus leucogaster, and Philantomba congica, (ii) two species are mostly diurnal: C.callipygus and C. nigrifrons, (iii) one species is strongly nocturnal: C.castaneus, (iv) and one species is mostly nocturnal: C.silvicultor. Analyses of temporal activities (for five species) identified four species pairs that highly overlapped (Δ^≥ 0.80), and six pairs that weakly overlapped (Δ^ between 0.06 and 0.35). Finally, co-occurrence tests reveal a truly random co-occurrence (plt > 0.05 and pgt > 0.05) for six species pairs, and a positive co-occurrence (pgt < 0.05) for four pairs. Positive co-occurrences are particularly noted for pairs formed by C.callipygus with the other species (except C. nigrifrons). These results are essential for a better understanding of the coexistence of duikers and the ecology of poorly known species (C. leucogaster and C. nigrifrons), and provide clarification on the activity patterns of C. silvicultor which was subject to controversy. Camera traps proved then to be a powerful tool for studying the activity patterns of free-ranging duiker populations.